CHRYSANTHEMUM AND GAILLARDIA AS STUNTED WINTER ANNUALS I. TRICOLOR CHRYSANTHEMUM (CHRYSANTHEMUM CARINATUM SCHOUSB.) - Sayed Shahin; Tarek Noor El-Deen; Boshra El-Sayed (Scientific Journal of Flowers and Ornamental Plants, 2014)
Chrysanthemum carinatum Schousb. is a tall annual herb with a thin, weak stems suffers from slanting, but it is used excessively in Egypt for beautifying of beds and borders. So, a study was conducted at Orman Botanical Garden, Giza, Egypt during 2012/2013 and 2013/2014 seasons to reveal the effect of foliar spraying with either paclobutrazol (PP-333) at the rates of 0, 50 and 100 ppm or cycocel (CCC) at the rates of 0, 1000 and 2000 ppm, twice with 3 weeks interval on growth performance, flowering and quality of 75-days-old seedlings of Chrysanthemum carinatum grown in 15-cm-diameter plastic pots filled with about 1.5 kg of sand + clay mixture (1:1, v/v). The obtained results have shown that means of all vegetative and root growth parameters were significantly decreased as a result of spraying with either PP-333 or CCC at various levels of each. The low level of both did not reduce the size of plants to the optimum size, as they caused a reduction mostly ranged between 20-25% only. The high level of CCC (2000 ppm), however induced a great decrement in most growth criteria reached about 65% or more compared to control in the two seasons. So, the plants appear more compressing than required, and that was accompanied by crinkled and smaller leaves. On the other hand, the high level of PP-333 (100 ppm) gave the most suitable plant size going with the pot size without any disorders. Flowering was delayed and the other flowering characters were decreased by the low and high levels of the two used growth retardants with the different significance levels relative to control in both seasons, except for inflorescence diameter and its fresh and dry weights traits which were significantly increased in response to spraying with any concentration of PP-333. The shortest stalk length was scored by PP-333 at 100 ppm treatment and that was benefit in preventing head nutation in the dwarfed plants. The results also indicated that PP-333 at either level increased the leaf content of chlorophyll a and b, total soluble sugars, total indoles and total phenols, but decreased content of carotenoids. On the other side, CCC treatments decreased content of chlorophyll a and b, total soluble sugars and total indoles but raised content of carotenoids and total phenols.    Accordingly, it is recommended to spray the foliar of 75-days-old seedlings of Chrysanthemum carinatum Schousb. cultivated in 15-cm-diameter plastic pots with PP-333 aqueous solution at the rate of 100 ppm, twice with 3 weeks interval to get a unique flowering-pot-plant suitable for commercial marketing.